Influence of foliar-applied phosphorus and potassium on photosynthesis and transpiration of ‘Golden Delicious’ apple leaves (Malus domestica Borkh.) - Robert VEBERIČ; Dominik VODNIK; Franci ŠTAMPAR (Acta Agriculturae Slovenica, 2005)
The influence of foliar-applied phosphorus (P) and potassium (K) on leaf photosynthesis, transpiration and water use efficiency during the season was studied in Malus domestica ‘Golden Delicious’. The research was carried out on 14-year-old trees on M9 rootstocks. Trees were either sprayed with PK (Hascon M 10 AD), P (Radicon) or K fertiliser (Krad) or left unsprayed (control). PK spraying improved leaf potassium content and postponed the seasonal decrease in leaf potassium concentration. In other treatments, on the other hand, fertilizers were less effective in terms of leaf nutrient concentration enhancement. In general P, and to a lesser extent PK, spraying resulted in reduced leaf photosynthesis and transpiration to the K and control treatments. High leaf photosynthetic and transpiration rates were measured in the control. Trees sprayed with PK showed the highest water use efficiency during the summer period, which could be a benefit in response to water stress, frequently experienced under given climate.